2015
DOI: 10.1073/pnas.1512386112
|View full text |Cite
|
Sign up to set email alerts
|

Fate of MgSiO 3 melts at core–mantle boundary conditions

Abstract: One key for understanding the stratification in the deep mantle lies in the determination of the density and structure of matter at high pressures, as well as the density contrast between solid and liquid silicate phases. Indeed, the density contrast is the main control on the entrainment or settlement of matter and is of fundamental importance for understanding the past and present dynamic behavior of the deepest part of the Earth's mantle. Here, we adapted the X-ray absorption method to the small dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 29 publications
(29 reference statements)
8
80
1
Order By: Relevance
“…A few extant studies using static compression are limited to upper mantle conditions (e.g., Matsukage et al, 2005). While experiments using diamond anvil cells can reach up to Earth's core mantle boundary (CMB) pressure, only MgSiO 3 glass (an analog of MgSiO 3 melt) has been measured at ambient temperature (Petitgirard et al, 2015). Dynamic (shock-wave) experiments can directly determine the equation of state of silicate melts at simultaneous high pressure-high temperature conditions, but these measurements have so far focused on water-free systems, such as molten MgSiO 3 (Akins, 2004;Mosenfelder et al, 2009), Mg 2 SiO 4 (Mosenfelder et al, 2007), and Fe 2 SiO 4 (Thomas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A few extant studies using static compression are limited to upper mantle conditions (e.g., Matsukage et al, 2005). While experiments using diamond anvil cells can reach up to Earth's core mantle boundary (CMB) pressure, only MgSiO 3 glass (an analog of MgSiO 3 melt) has been measured at ambient temperature (Petitgirard et al, 2015). Dynamic (shock-wave) experiments can directly determine the equation of state of silicate melts at simultaneous high pressure-high temperature conditions, but these measurements have so far focused on water-free systems, such as molten MgSiO 3 (Akins, 2004;Mosenfelder et al, 2009), Mg 2 SiO 4 (Mosenfelder et al, 2007), and Fe 2 SiO 4 (Thomas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This well-established technique allows us to measure density of liquid under desired pressure and temperature conditions with much improved precision and accuracy. The technique is also applied to diamond anvil cell for density measurement of silicate glasses at much higher pressures (Sato and Funamori, 2008;Petitgirard et al, 2015). Jadeite (NaAlSi 2 O 6 ) is a basic sodium aluminosilicate and one of the important mantle minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Silicate glasses have been used as possible analogs for silicate melts to understand the nature of dense magmas in the lower mantle (e.g., Bass 2010, 2011;Petitgirard et al 2015). Although the structural changes that silicate glasses undergo cannot be assumed to be a completely valid model for silicate melts, previous experimental works have shown that the Si-O coordination numbers of SiO 2 glass and a molten basalt appear to change in generally similar ways (Meade et al 1992;Lin et al 2007; Funamori 2008, 2010;Benmore et al 2010;Zeidler et al 2014;Sanloup et al 2013).…”
Section: Introductionmentioning
confidence: 99%